Experiences of Harassment, Discrimination, and Physical Violence Among Young Gay and Bisexual Men - Huebner, David M. (© American Journal of Public Health 2004, 2004)
Objectives. We examined the 6-month cumulative incidence of anti-gay harassment, discrimination, and violence among young gay/bisexual men and documented their associations with mental health. Methods. Gay/bisexual men from 3 cities in the southwestern United States completed self-administered questionnaires. Results. Thirty-seven percent of men reported experiencing anti-gay verbal harassment in the previous 6 months; 11.2% reported discrimination, and 4.8% reported physical violence. Men were more likely to report these experiences if they were younger, were more open in disclosing their sexual orientation to others, and were HIV positive. Reports of mistreatment were associated with lower self-esteem and increased suicidal ideation. Conclusions. Absent policies preventing anti-gay mistreatment, empowerment and community-building programs are needed for young gay/bisexual men to both create safe social settings and help them cope with the psychological effects of these events.